Financial characteristics of the nonprofit organisation: theory and evidence for the assessment of the financial condition of South African public universities - Bunting, Mark Bevan (Rhodes University, Faculty of Commerce, Department of Accounting, 2016)
In this thesis, an analytical framework is developed for the assessment of the financial condition of South African public universities. Foundational constructs of nonprofit economics are applied in the consideration of financial theories of nonprofit organisations in general, and public universities in particular. From this review, a number of hypotheses are developed. Each of these specifies a positive or negative association between a university's financial condition and a particular dimension of its assets, liabilities, equity, revenues, expenses and surplus. From the nonprofit financial analysis literature, ratios and indicators relevant to these hypotheses are selected. Audited data from the annual financial statements of the universities for the seven year period 2007 to 2013 are substantially transformed in mitigation of failures in accounting, auditing and accountability. The adjusted accounting numbers are used to calculate the financial indicators applicable to each university. Exploratory factor analysis is implemented to categorise and organise this large indicator set on the basis of identified associations with a smaller number of factors. It is found that the financial condition of South African public universities is defined by two broad financial characteristics, capital and revenue. Assessment of the capital dimension is informed by a focus on institutional equity, with particular emphasis on expendable equity and its proportionate relationships with surplus, total capital, and total expenses. The revenue dimension is appropriately evaluated in the context of a comparative and interactive consideration of the three main components of South African public university revenue, as well as the proportionate relationship between non-staff operating expenses and total expenses. The framework displays considerable levels of stability and consistency over the seven year review period, and its constructs are, in addition, robust to the application of multiple alternative confirmatory tests involving financial data that are independent of the factor solutions. The financial condition assessment framework developed in this thesis offers a contribution to a broader discourse in nonprofit finance and accounting, with a focus on public university finances.
Keywords: Uncatalogued